(untitled) (Global Journals of Research in Engineering, 2020)
Integration of Distributed Generations (DGs) at distribution network levels have changed the structure from being radial to mesh; thereby causing fault currents to be fed from all the sources connected to the network. Another operational requirement is that DGs can get disconnected from the network due to disturbances or maintenance requirements leading to new network topology. This research work has, therefore, proposed an adaptive protection scheme that relies on modern communication infrastructure for its implementation, after optimally siting and sizing of DG and investigation of impact of DG on the protection system and reliability of the system. Herein, modified particle swarm optimization (MPSO) has been deployed for the optimal relay parameters values (operation time, pick up current and time dial settings). Standard communication protocol (IEC 61850) has been chosen to facilitate the communication amongst the various devices in the adaptive protection framework developed.